Correction to the Number of Theoretical Plates and Resolution Equation for Capillary Zone Electrophoresis and Micellar Electrokinetic Capillary Choromatography - Ghowsi, Kiumars; Ghowsi, Hosein (Asian Journal of Chemistry, 2011)
A new model based on effective length migrated on a similar to tread mill case for various modes of operation in capillary zone electrophores has been constructed. New resolution and number of theoretical plates for capillary zone electrophoresis have been proposed. Similar treatment has been applied to micellar electrokinetic capillary chromatography and new equations obtained for the number of theoretical plates and resolution equations for various cases of operation.